NATIONAL SECURITY STRATEGY IN THE FIELD OF CYBER AND CRYPTOGRAPHY THROUGH ELECTRONIC CERTIFICATION SERVICES - Agung Arafat Saputra; Oksidelfa Yanto (Jurnal Hukum Mimbar Justitia, 2023)
The rise of cybercrime has caused the public to worry about criminal acts of theft and falsification of personal data in electronic form. Therefore, the government is obliged to provide protection to the public from all forms of disturbances caused by misuse of information technology and digital transactions. Based on this, this research aims to find out and understand what are the obstacles for BSRE as an agency providing electronic certificate management services which cannot provide services in general. Then, does BSRE's authority to provide general electronic certificate services to the public conflict with statutory regulations? The method used in preparing this research is the Normative Law research method with the data source, namely secondary data collected through literature study. The research results show that the obstacle for BSrE as an agency providing electronic certificate management services is that it cannot provide services in general because it is still separated by agency and non-agency provisions which limit the scope of BSrE in providing electronic certificate services to the public/general public. Furthermore, BSrE as an electronic Certification Organizer only serves the public as Indonesian citizens who have the status of government or agency employees.  Keywords: Security Strategy; Certification; Electronics.